2017
DOI: 10.1007/s00125-017-4346-8
|View full text |Cite
|
Sign up to set email alerts
|

Age at natural menopause and risk of type 2 diabetes: a prospective cohort study

Abstract: Aims/hypothesis In this study, we aimed to examine the association between age at natural menopause and risk of type 2 diabetes, and to assess whether this association is independent of potential mediators. Methods We included 3639 postmenopausal women from the prospective, population-based Rotterdam Study. Age at natural menopause was self-reported retrospectively and was treated as a continuous variable and in categories (premature, <40 years; early, 40-44 years; normal, 45-55 years; and late menopause, >55 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
2
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 50 publications
1
62
2
7
Order By: Relevance
“…Previous studies have suggested that premature and early natural menopause are associated with subsequent risk of diabetes. 34 Most recently, data from the Rotterdam Study showed a 3-fold increased risk of diabetes for women who experienced premature menopause compared with those who experienced menopause after the age of 55 years, although the number of incident cases of diabetes in both groups (n = 29) was much smaller than in the present study. Previous authors have speculated on possible genetic mechanisms linking early age at menopause (possibly a proxy for premature ageing and DNA damage) with risk of incident diabetes and other chronic, age-related conditions.…”
Section: Discussioncontrasting
confidence: 69%
“…Previous studies have suggested that premature and early natural menopause are associated with subsequent risk of diabetes. 34 Most recently, data from the Rotterdam Study showed a 3-fold increased risk of diabetes for women who experienced premature menopause compared with those who experienced menopause after the age of 55 years, although the number of incident cases of diabetes in both groups (n = 29) was much smaller than in the present study. Previous authors have speculated on possible genetic mechanisms linking early age at menopause (possibly a proxy for premature ageing and DNA damage) with risk of incident diabetes and other chronic, age-related conditions.…”
Section: Discussioncontrasting
confidence: 69%
“…However, it is worth noting that some other studies examining the association between age at menopause and diabetes have yielded completely contradictory results, showing that early menopause is associated with a greater risk of type 2 diabetes. Most recently, Muka et al ,. in a prospective, population‐based study, confirmed the increased risk of type 2 diabetes with early onset menopause in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Слід зазначити, що жінки старші 45 років хворіють на ЦД в 2 рази частіше за чоловіків [16]. Частота виникнення ЦД у жінок після 50 років значно збільшується і, на дум-ку більшості фахівців, менопауза певним чином впливає на підвищення його поширеності серед жінок старшої вікової групи [13,19].…”
Section: Ibolit@iuaunclassified